1997
DOI: 10.1037/0735-7028.28.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Well-functioning in professional psychologists.

Abstract: Experienced professional psychologists identified factors that contributed to their ability to function well in Study 1, through interviews with 6 well-functioning psychologists, and in Study 2, through questionnaire responses from 339 randomly selected licensed psychologists. Collectively they highlighted self-awareness and monitoring; support from peers, spouses, friends, mentors, therapists, and supervisors; values; and a balanced life, Including vacations and other stress-reducers. Discussion focuses on st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
180
2
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(192 citation statements)
references
References 34 publications
(34 reference statements)
8
180
2
2
Order By: Relevance
“…Among studies that have assessed practitioner selfcare, Mahoney (1997) found the most commonly used behaviors were reading for pleasure, exercising, taking vacations, having a hobby, supervising peers, and praying or meditating. In a series of studies by Coster and Schwebel (1997) and Schwebel and Coster (1998), practitioners and heads of psychology programs reported the factors that contributed to preventing and coping with stress ("wellfunctioning," p. 284) included self-awareness, balance between personal and professional lives, relationships with family and partners, and personal values. Skovholt et al (2001) stated that " [C]ounselor training, congruent with the nature of the work and the people in it, is predominantly other-focused…with relatively little attention given to care for the self" (p. 168).…”
Section: Self-carementioning
confidence: 99%
“…Among studies that have assessed practitioner selfcare, Mahoney (1997) found the most commonly used behaviors were reading for pleasure, exercising, taking vacations, having a hobby, supervising peers, and praying or meditating. In a series of studies by Coster and Schwebel (1997) and Schwebel and Coster (1998), practitioners and heads of psychology programs reported the factors that contributed to preventing and coping with stress ("wellfunctioning," p. 284) included self-awareness, balance between personal and professional lives, relationships with family and partners, and personal values. Skovholt et al (2001) stated that " [C]ounselor training, congruent with the nature of the work and the people in it, is predominantly other-focused…with relatively little attention given to care for the self" (p. 168).…”
Section: Self-carementioning
confidence: 99%
“…The physical component is defined as undertaking motor activity, which results in expending energy via exercises, sport, household and daily functioning activities (Henderson, Ainsworth, 2001). The psychological component refers to seeking specialist support in tackling psychological problems and improving one's competences of coping with stress (Coster, Schwebel, 1997). Spiritual element is related to looking for a sense of purpose and meaning in life (Hage, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies have suggested that there is confusion among clinical supervisors regarding CS and line and performance management, 4,6 our respondents made the clear distinction that CS was a supportive and reflective relationship that was separate from the organisation imperatives for performance management. This is linked to a previous study that has suggested that self-reflection and selfmanagement are important factors for the well being of professional psychologists 31 and this may apply to other allied health professions.…”
Section: Implications For Safety and Quality In Allied Health Practicementioning
confidence: 99%